THE CONCEPT, STRUCTURE, AND DIDACTIC FEATURES OF STUDENTS’ INDEPENDENT LEARNING (European Journal of Pedagogical Initiatives and Educational Practices, 2026)
This article examines the concept, structure, and didactic features of students’ independent learning in modern educational systems. Independent learning is considered a key factor in developing students’ critical thinking, self-regulation, and lifelong learning skills. The paper analyzes the main components of independent learning, including motivation, cognitive activity, and self-assessment. Furthermore, special attention is given to the didactic conditions and methods that enhance the effectiveness of independent study. The study highlights the importance of integrating innovative teaching technologies and learner-centered approaches to foster autonomy and responsibility among students.